A comparative study of the psychological traits and group cohesion traits among the playing lines of young football players under (20) years of age - Ali , Jihad; Malik , Faris; Dahi , Nuha (Journal of Physical Education, 2025)
This study investigates the differences in psychological climate and group cohesion across different playing lines (defense, midfield, attack, and goalkeepers) among youth football players under 20 years of age in the Iraqi Premier League. Recognizing the critical role psychological factors play in athletic performance, the researchers aimed to determine how these variables vary based on players' field positions.A descriptive comparative approach was employed, involving a purposive sample of 148 players (representing 75.51% of the research population). Two validated scales were used: the Psychological Climate Scale (Al-Hayali, 2011) and the Group Cohesion Scale (Alawi, 1984). Data were analyzed using descriptive statistics, one-way ANOVA, and the LSD test for post hoc comparisons.Findings revealed statistically significant differences in psychological climate among playing lines, particularly between midfielders and both defenders (p = 0.011) and attackers (p < 0.001), favoring attackers. No significant differences were found in group cohesion across the playing lines (p > 0.05). These results suggest that midfielders experience distinct psychological pressures due to their pivotal role in connecting defense and attack, potentially affecting their perception of the team environment.The study underscores the importance of tailored psychological training and leadership strategies that consider positional roles. Enhancing psychological climate—especially among midfielders—may contribute to improved performance and team synergy. Coaches are encouraged to promote balanced cohesion and address psychological disparities to foster a unified and mentally resilient team.